Aesthetic Surgery Training and Practice in India: A Survey - Abizer Kapadia; Mahesh Nair (Indian Journal of Plastic Surgery)
Introduction Aesthetic surgery is a rapidly evolving subspecialty in high demand worldwide. To be considered a fully trained plastic surgeon, all the requirements of the curriculum must be met through to successful completion, including aesthetic surgery. At present, a disparity exists between the demand and provision of aesthetic surgery training in India. This survey evaluation highlights the responses, concerns, and possible solutions regarding training and practice of cosmetic surgery in India.